ANALYSIS PERFORMANCE OF THE BROILER FARM BUSINESS AT PARTNERSHIP MODEL WITH OF THE OPENED HOUSE SYSTEM (Case Study In Baluk Village, Negara District) - N. M. D., Maharatih; Sukanata, I W.; Astawa, I P. A. (Jurnal Peternakan Tropika, 2017)
A research had been carried out to determine performance of production and income of boiler business on the partnership model using opened house system for two month in plasma farmer was located in Baluk Village, Negara district, Jembrana Regency. The data used in this research is production data for 8 period from February 2016 - March 2017. The data of the first seven periods are secondary data while the eight period data is the primary data. The variables observed in this study are business profile, maintenance management, average harvest age, weight gain, FCR, index performance and depletion. Research data were analyzed by descriptive and quantitative method. In this model, the average cattle at age 30 days with an average body weight of 1.66 kg / head, weight gain of 1.62 kg / head or 53.62 gram / head / day, the value of FCR 1, 62, index performance 325.53 and the average depletion of 6.34%. The results of this study indicate was used average performance of broiler chickens in partnership model with open house system in Baluk Village, Negara district wasstill below standard, so the result was not maximal Key words: performance, broiler chicken, partnership model, open house.